TWIST mediates resistance to paclitaxel by regulating Akt and Bcl-2 expression in gastric cancer cells - Chae Hwa Kwon; Hye Ji Park; Yuri Choi; Yeo Jin Won; Seon Jin Lee; Do Youn Park (Tumor Biology)
The transcription factor TWIST has been reported to play an important role in tumor progression as well as resistance to anti-cancer drugs. However, the role of TWIST in gastric cancer and the molecular mechanisms by which this protein elicits drug resistance remain poorly understood. We transfected gastric cancer cell lines with lentiviral vector to generate TWIST-overexpressing stable cell lines. Our study showed that overexpression of TWIST not only increased cell migration and invasion but also induced resistance to the anti-cancer drug paclitaxel in gastric cancer. Paclitaxel increased gastric cancer cell death in dose-dependent manner; this was decreased following TWIST overexpression. Furthermore, treatment with paclitaxel decreased Akt phosphorylation and Bcl-2 expression, whereas these effects were suppressed by TWIST overexpression. Treatment of cells with Akt inhibitor or small interfering RNA targeting for Bcl-2 led to increased paclitaxel-induced cell death, indicating that TWIST elicits resistance to paclitaxel via the regulation of the Akt and Bcl-2 pathway. Our results suggest an underlying mechanism for TWIST-mediated paclitaxel resistance and indicate that TWIST represents a potential target for overcoming paclitaxel resistance in gastric cancer cells.